Heritability estimates for Merino sheep obtained from a national progeny test - Groenewald, P.G.J.; Olivier, J.J.; Olivier, W.J. (African Journals Online, 1999)
Data of 5342 progeny from 232 sires from 30 genetically linked flocks, collected through the National Progeny Testing program for Merino sheep from 1991 to 1996, were used to estimate heritabilities for several production and type traits. The traits analysed were: body weight (BW), clean fleece weight (CFW), mean fibre diameter (MFD), staple length (SL), fold (wrinkle) score (FS), wool quality (QUAL), variation crimps per 25 mm (VAR), wool yolk (OIL), staple formation (SF), belly and points, (BP), head size (HEA~), colour (COL), fore quarters (FQ), pasterns (PAS), hocks (HOC) and conformation (CON). In most traits the effect of herd-year-season"' (HYS) was significant (P ~ 0.01). For the production traits, excluding MFD, the interaction between HYS and sex was significant. Birth status had no significant (P¡Ý 0.05) effect on QUAL, OIL, SF, COL and PAS. Heritability estimates for the various traits were: 0.34 for BW, 0.23 for CFW, 0.44 for MFD, 0.70 for SL, 0.32 for FS, 0.27 for QUAL, 0.23 for VAR, 0.24 for OIL, 0.09 for SF, 0.17 for BP, 0.35 for HEAD, 0.17 for COL, 0.21 for FQ, 0.12 for PAS, 0.26 for HOC and 0.31 for CON. Standard errors for these estimates ranged from 0.03 to 0.06. It is recommended that these heritability estimates be used in the calculation of selection index weighting factors, as well as EPD's in the National Progeny Testing Scheme.